The Development of Thermal Insulation from Oil Palm Waste Material - Mohd Aizzat Bin Omar, Mohd Aizzat (Universiti Teknologi Petronas, 2010)
Thermal insulation can refer to those materials and combinations of materials used to reduce the rate of heat transfer, or the method and processes used to retard the flow of heat energy. Thermal insulation has been used on many applications such as pipe insulation, window insulation, building insulation, and clothing. The problem of managing the abundantly oil palm waste material has become critical for the manufacturers. Thus, by utilized the wastes as useful products can contribute to on how to manage the abundantly wastes materials.